Improving Students’ Writting Skill Using Jumbled Sentences At Eight Grade Students In MTs Model Samarinda - Muliyandari, Atika (Faculty of Education and Teacher Training of UINSI Samarinda, 2022)
Abstract Writing is one of the skill that students should master because in writing students can express their ideas, but writing is regarded to be the most difficult skill among the four skills. The students in MTsN Model Samarinda have an under standard score for minimum completion (KKM). The students who got score under 80 are60% and there were 40% who got score above criteria for minimum completion. Furthermore, the researcher wants the students to get 85% as criteria of success for the students in writing skill by using jumbled sentences at the eighth grade of MTsN Model Samarinda in academic year 2015/2016. This research used classroom action research (CAR) procedure that adapted from Kemmis and Mc. Taggart. It was conducted in 2 cycles and the procedures of this classroom action research were planning, acting, observing, and reflecting. The criteria of success of this research is 85% of students get score test 80 based on the standard score criteria for minimum completion (KKM) and most of students are actively involved during teaching and learning process.Based on the analysis results, the jumbled sentences can improve students’ writing skill. It can be proved in preliminary study, the average score is 40 and only 15 students who got score above 80. In cycle 1 there was significant improvement with average score 79.3 then in cycle 2 there was an improvement score was 85 and all of the students got the score above 80 so students were actively involved in teaching learning process. Keywords: Writing Skill, Jumbled Sentences, Classroom Action Research (CAR) Abstrak Menulis merupakan salah satu keterampilan yang harus dikuasai siswa karena dalam menulis siswa dapat mengungkapkan gagasannya, namun menulis dianggap keterampilan yang paling sulit di antara keempat keterampilan tersebut. Siswa di MTsN Model Samarinda memiliki nilai ketuntasan minimal (KKM) di bawah standar. Siswa yang mendapat nilai di bawah 80 sebanyak 60% dan ada 40% yang mendapat nilai di atas kriteria ketuntasan minimal. Selanjutnya, peneliti menginginkan siswa mendapatkan 85% sebagai kriteria keberhasilan siswa dalam keterampilan menulis dengan menggunakan kalimat acak di kelas delapan MTsN Model Samarinda tahun ajaran 2015/2016. Penelitian ini menggunakan prosedur penelitian tindakan kelas (PTK) yang diadaptasi dari Kemmis dan Mc. Taggart. Penelitian ini dilaksanakan dalam 2 siklus dan prosedur penelitian tindakan kelas ini adalah perencanaan, tindakan, observasi, dan refleksi. Kriteria keberhasilan penelitian ini adalah 85% siswa mendapatkan skor tes 80 berdasarkan kriteria skor standar ketuntasan minimal (KKM) dan sebagian besar siswa terlibat aktif selama proses belajar mengajar. Berdasarkan hasil analisis, kalimat campur aduk dapat meningkatkan kemampuan menulis siswa. Hal ini dapat dibuktikan pada studi pendahuluan nilai rata-rata 40 dan hanya 15 siswa yang mendapat nilai di atas 80. Pada siklus 1 terjadi peningkatan yang signifikan dengan nilai rata-rata 79,3 kemudian pada siklus 2 terjadi peningkatan nilai 85 dan semua siswa mendapat nilai di atas 80 sehingga siswa terlibat aktif dalam proses belajar mengajar. Kata kunci: Keterampilan Menulis, Kalimat Jumbled, Penelitian Tindakan Kelas (PTK)